Consumers economic behavior and emotions: the case of iphone 6 in neuromarketing - Neto, J. C.; Filipe, J. A. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
In the current era, consumers’ fascination for many notable brands in the market is rising considerably. This effect shows that many companies are trying to consistently reproduce this effect in their current (and potential) customers and thus look for creating a strong identification with their brand(s), what allows the company to add new economic value. However, the vast majority of these companies finds limitations in the way traditional marketing works to achieve a necessary emotional state for the generation of a brand identification. Thus it is necessary to go further and use more effective tools for the study of consumer behavior. An interesting possibility is the use of Neuromarketing, emphasizing research methods for studying people’s emotion feelings, by facing stimuli related to a specific brand. From this analysis, companies may adjust their commercial and economic strategy to take advantage from their brands competitive positioning in the market.